PENINGKATAN KOMPETENSI TERHADAP KINERJA APARATUR PEMERINTAH PADA DINAS SOSIAL PROVINSI JAWA TIMUR - Achmad Resa Fachrizi (REFORMASI, 2019)
The performance targets of employees in the East Java Social Service Agency are not all can be fulfilled. The competence of the Social Service personnel still needs to be improved, considering it as an agency that has the main task to provide services and social rehabilitation for people with social welfare problems. The purpose of this study was to analyze how the competence of employees of the Social Service could be increased and examine the factors that influence the improvement of employee competencies. This research is a descriptive qualitative. The sampling technique used a purposive sampling. The informants were the Head of the Social Service, the Secretary and all Heads of Fields of the Social Service Agency. The results of the study showed that the increase in competence of Social Service personnel was not optimal. This was caused by the inhibiting factors such as trust and value, expertise, experience, personal characteristics, motivation, emotional issues and intellectual capacity. It can be concluded that the efforts to increase personnel competence were limited to attending work meetings, technical meetings, congresses, seminars, technical guidance and workshops. The minimum indicators of knowledge relating to tasks, principal and functions, work programs and stages in carrying out work programs were not all understood by the Social Service apparatus. For skills indicators that must be owned by the them are the ability to compile, managing, evaluating the programs and performance, managing finances and assets, communication skills, adaptability and managing archives and information. Keywords: Competency, Apparatus, Government. Sasaran kinerja pegawai pada Dinas Sosial Provinsi Jawa Timur tidak semuanya dapat terealisasi sesuai target. Kompetensi personil Dinas Sosial masih perlu ditingkatkan, mengingat Dinas Sosial merupakan instansi yang memiliki tugas pokok terhadap pelayanan dan rehabilitasi sosial terhadap penyandang masalah kesejahteraan sosial. Tujuan dalam penelitian ini menganalisa sejauh mana peningkatan kompetensi pegawai Dinas Sosial serta mengkaji faktor-faktor yang mempengaruhi peningkatan kompetensi pegawai. Jenis penelitian yang digunakan adalah kualitatif deskriptif. Teknik pengambilan sampel menggunakan purposive sampling, Informan adalah Kepala Dinas Sosial, Sekretaris serta seluruh Kepala Bidang yang ada di Dinas Sosial. Hasil penelitian menunjukkan bahwa peningkatan kompetensi terhadap personil Dinas Sosial masih belum maksimal. Hal ini disebabkan oleh faktor penghambat, antara lain: Kepercayaan dan nilai, keahlian, pengalaman, karakteristik personal, motivasi, isu-isu emosional dan kapasitas intelektual. Kesimpulannya bahwa peningkatan kompetensi yang dilakukan terhadap personil Dinas Sosial sebatas pada mengikuti rapat kerja, rapat teknis, kongres, seminar, bimbingan teknis dan workshop. Indikator pengetahuan minimal aparatur Dinas Sosial yang berkaitan dengan tugas, pokok dan fungsi, program kerja dan tahapan-tahapan dalam melaksanakan program kerja tidak semua personil memahaminya. Untuk indikator keterampilan yang harus dimiliki adalah kemampuan menyusun, mengelola, mengevaluasi program dan kinerja, mengelola keuangan dan aset, kemampuan berkomunikasi, kemampuan beradaptasi serta mengelola kearsipan dan informasi. Kata Kunci: Kompetensi, Aparatur, Pemerintah.